Amiodarone Pulmonary, Neuromuscular and Ophthalmologic Toxicity - Karen EA Burns; Eugenia Piliotis; Bertha M Garcia; Kathleen A Ferguson (Canadian Respiratory Journal)
Amiodarone is an iodinated benzofuran derivative class III antiarrhythmic that is highly effective in suppressing ventricular and supraventricular arrhythmias. It is also associated with an imposing side effect profile, which often limits its use. Numerous adverse effects have been documented including skin discolouration, photosensitivity, hepatitis, thyroid dysfunction, corneal deposits, pulmonary fibrosis, bone marrow suppression and drug interactions. These side effects are thought to be correlated with the total cumulative dose of amiodarone, but idiopathic reactions have been reported. The majority of adverse reactions resolve with discontinuation of the drug; however, rapid progression may occur, which may be fatal. The present report documents a patient who had a combination of serious amiodarone toxicities that, once recognized, were treated and eventually resulted in a good outcome.